Ecological Momentary Mood, Resilience, and Mental Health Status as Predictors of Quality of Life Among Young Adults Under Stress: A Structural Equation Modeling Analysis - Sinvani, Rachel-Tzofia; Fogel-Grinvald, Haya; Afek, Anat; Ben-Avraham, Rina; Davidov, Alex; Cohen, Noa Berezin; Ben Yehuda, Ariel; Nahum, Mor; Gilboa, Yafit (Frontiers in Psychiatry, 2021)
Multiple internal factors, such as psychological resilience and mental health status, have been shown to contribute to the overall quality of life (QoL). However, very few studies to date have examined how these factors contribute to QoL of youth and young adults in a stressful situation. Here, we studied the contribution of these factors, as well as of ecological momentary mood assessment, to QoL of young army recruits during their Basic Training Combat (BCT). To this end, we collected data from 156 male and female soldiers in a mixed-gender unit in the Israel Defense Forces (IDF) during their BCT. Using a mobile app installed on participants’ phones, participants provided self-reports regarding their mental health status and psychological resilience at baseline, and QoL two weeks later. Momentary mood reporting was further collected during the 2-week interval period using a daily self-report mood scale (IMS-12). Structural equation modeling (SEM) was used to examine the interrelationships among the study variables based on a hypothesized model. We found that a model with all factors (gender, resilience, mental health status and momentary mood) provided a good fit for the data based on its fit indices (Χ²(38)=47.506, p=.139, CFI=.979, NFI=.910, RMSEA=.040, TLI=.964). However, the only direct contributors to QoL were gender and momentary mood, accounting together for 61.5% of the variance of QoL. Psychological resilience and mental health status contributed to QoL only indirectly, through their associations with momentary mood. Collectively, these results highlight the importance of ecological momentary assessment of mental-health related factors such as mood to the prediction of QoL in young adults under stress. These findings may have broader implications for monitoring and improvement of wellbeing in young healthy populations as well as in clinical ones.